An online database of infant functional near infrared spectroscopy studies: a community-augmented systematic review. - Alejandrina Cristia; Emmanuel Dupoux; Yoko Hakuno; Sarah Lloyd-Fox; Manuela Schuetze; José Kivits; Tomas Bergvelt; Marjolijn van Gelder; Luca Filippin; Sylvain Charron; Yasuyo Minagawa-Kawai (PLoS ONE)
Until recently, imaging the infant brain was very challenging. Functional Near InfraRed Spectroscopy (fNIRS) is a promising, relatively novel technique, whose use is rapidly expanding. As an emergent field, it is particularly important to share methodological knowledge to ensure replicable and robust results. In this paper, we present a community-augmented database which will facilitate precisely this exchange. We tabulated articles and theses reporting empirical fNIRS research carried out on infants below three years of age along several methodological variables. The resulting spreadsheet has been uploaded in a format allowing individuals to continue adding new results, and download the most recent version of the table. Thus, this database is ideal to carry out systematic reviews. We illustrate its academic utility by focusing on the factors affecting three key variables: infant attrition, the reliability of oxygenated and deoxygenated responses, and signal-to-noise ratios. We then discuss strengths and weaknesses of the DBIfNIRS, and conclude by suggesting a set of simple guidelines aimed to facilitate methodological convergence through the standardization of reports.